STUDY ON ENVIRONMENTAL QUALITY AND HAZARD IDENTIFICATION OF UNDERGROUND COAL GASIFICATION PROJECT: A LITERATURE STUDY AND FIELD SURVEY - Retno Damayanti (Puslitbang tekMIRA, 2018)
Underground coal gasification (UCG) is a procedure to extract synthesis gas (syngas) from the insitu underground coal seams that could not be extracted by conventional mining methods. This is a clean technology as an alternative method for direct insitu coal conversion. This process involves some heavy equipment and complex operation. Hazards identification and risk assessment in the UCG Project involve identifying the environmental hazards that cover physical, chemical and biological environments to predict the process sequences, its frequency as well as consequences that lead to those hazards. The assignment of risk level is also conducted to design corrective action in minimizing the risk or eliminating the hazards. The environmental condition of the project plan is generally good with the fulfillment of the established environmental quality standards.